The Development of Project-Based E-Learning Tool to Improve Students' Creative Thinking Skill - Nurul Qomariyah Ahmad; Bettri Yustinaningrum (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
This study aimed to determine the form, the level of effectiveness, and the obstacles and challenge in developing project-based e-learning tool to improve students’ creative thinking skills. The learning media developed are syllabus, lesson plans, modules, and creative thinking skills test. The model which is developed is the Plomp model which consists of some phases namely investigation, design, realization/construction phases and the evaluation, revision, test phase. Based on the validation test, the syllabus was 4.48, the RPS was 4.48, the module was 4.36, and the THB was valid. Based on the practicality test, the students’ responses were 76.25% and the lecturers’ responses were 4.70 and the category is very good. Based on the individual effectiveness test of 43.8% > 5%, classical completeness z count = 0.976 is between the z table and the N-gain test, 2 students had increasing creative thinking ability test scores in the high category, 6 students were in the medium category. Then it can be concluded that the learning tools developed are valid, effective, and practical.